Clinical and Biological Significances of a Ferroptosis-Related Gene Signature in Glioma - Zhuo, Shenghua; Chen, Zhimin; Yang, Yibei; Zhang, Jinben; Tang, Jianming; Yang, Kun (Frontiers in Oncology, 2020)
Ferroptosis is a form of cell death characterized by non-apoptosis induced by small molecules in tumors. Studies have demonstrated that ferroptosis play key roles in the biological behaviors of tumors. Therefore, genes that control ferroptosis can be a promising candidate bioindicator in tumor therapy. Herein, functions of ferroptosis-related genes in glioma remain elusive. As a result, we systematically assess the relationship between ferroptosis-related genes expression profiles and prognosis in glioma patients based on both The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) RNA sequencing datasets. During the assessment, the non-negative matrix factorization clustering (NMF) method was used on 84 ferroptosis-related genes from RNA sequencing where we distinctly identified two subgroups (named cluster 1 and cluster 2) in glioma. Besides, the least absolute shrinkage and selection operator (LASSO) was used in developing a 25 gene risk signature. Moreover, the relationship between the gene risk signature and clinical features in glioma was in-depth examined. Thus, testing the risk Score association with glioma patients’ clinical and molecular features can be an independent prognostic indicator for glioma patients. Collectively, our results demonstrated that a ferroptosis-related risk signature can potentially predict the outcome of glioma patients.